Peroxisome Proliferator-Activated Receptor-&#947: Master Regulator of Adipogenesis and Obesity - Shao, Xiaoru; Wang, Meiqi; Wei, Xueqin; Deng, Shuwen; Fu, Na; Peng, Qiang; Jiang, Yan; Ye, Ling; Xie, Jiamin; Lin, Yunfeng (Current Stem Cell Research & Therapy, 2016)
Obesity, which is a key risk for the development of hyperglycemia, hypertension, hyperlipidemia and insulin resistance and is totally referred to as the metabolic disorders, has aroused people’s great attention because of its alarming increase rate around the world. It is widely known that the occurrence of obesity can be attributed to both environmental and genetic factors. Peroxisome proliferators- activated receptor (PPAR), a member of ligand-dependent receptor, is one of the important genetic factors. PPAR includes three isoforms: PPAR-α, PPAR- β and PPAR- γ, all of which are exerting critical influences on the maintenance of the metabolism of saccharides, lipids and proteins. PPAR-γ is of great importance in the regulation of adipogenesis; in addition, it is essential in the prevention of adiposis and the treatment of 2-diabetes mellitus. In this review, we focus on giving a brief introduction about PPAR family, the indispensible function of PPAR-γ in adipogenesis and the inseparable relationship between PPAR-γ and obesity, deriving from the understanding of how these receptors activated will provide windows of opportunities for the treatment of obesity and associated metabolism syndromes.
Keywords: Adipogenesis